Assessment of protein model structure accuracy estimation in CASP14: Old and new challenges. Issue 12 (5th August 2021) - Kwon, Sohee; Won, Jonghun; Kryshtafovych, Andriy; Seok, Chaok
Abstract: In CASP, blind testing of model accuracy estimation methods has been conducted on models submitted by tertiary structure prediction servers. In CASP14, model accuracy estimation results were evaluated in terms of both global and local structure accuracy, as in the previous CASPs. Unlike the previous CASPs that did not show pronounced improvements in performance, the best single‐model method (from the Baker group) showed an improved performance in CASP14, particularly in evaluating global structure accuracy when compared to both the best single‐model methods in previous CASPs and the best multi‐model methods in the current CASP. Although the CASP14 experiment on model accuracy estimation did not deal with the structures generated by AlphaFold2, new challenges that have arisen due to the success of AlphaFold2 are discussed.